Forgery: fake documents and its legal implications / Joplin Anak Jeffery, Hafizul Idham Abu Bakar, Maslin Kuyubin - Jeffery, Joplin Anak; Abu Bakar, Hafizul Idham; Kuyubin, Maslin (2008)
Almost all modern business and commerce transactions depend on documents, both papers and electronics, in orderto record and facilitate the particulars of the agreement taking place. Forgery is the crime of creating a false document, altering a document, or signing someone else's document with the intent to steal or to cheat a person, business, or governent agenc out of money, goods or services. While fraud is a closely related deception made for personal gain, forgery specifically uses documents with the intent to defraud and gain illegal benefits in a manner which abuses and challenges the social order. The reason we embarked upon this research is to study the factors which contribute to this problem and presents innovative solutions where such can be found. In this respect, we are looking at the efficacy, suitability and also adequacy of our Malaysian law namely the National Land Code 1965 as well as the Penal Code to deal with fraudulent land transfer involving forgery. Therefore, this issue must be determined and re-construct in order to restore the property to the owner as well as to ensure their rights upon the property and also to strengthen the law itself.